The influence of mass media in the protection of women through the implementation of regional regulation no. 5 of 2013 on the protection of women and children in west Sumatra province - Rahayu, Wewen Kusumi; Purwanti, Ani; Astuti, Retno Sunu; Lituhayu, Dyah (Edelweiss Applied Science and Technology, 2025)
Gender equality is still one of the things that must always be pursued by the government together with all elements in each region. Gender equality can be seen from cases of gender- based violence that still exist in an area. The rate of violence against women in West Sumatra Province is still considered high. In 2022 the number of violence against women was 216 cases and in 2023 it increased to 228 cases. The Regional Government of West Sumatra Province has taken various ways to reduce the number of violence against women and realize gender equality, namely by making a Women’s Protection policy, namely Regional Regulation No. 5 of 2013. Based on Regional Regulation No. 5 of 2013, the government collaborates with various stakeholders. This study looks at how collaboration between all elements in the protection of women in West Sumatra. This study uses quantitative methods to test the hypothesis about the influence of each stakeholder using Kendall’s Rank formula. The Penta Helix collaboration theory according to Ramesh and Howlett will be used to see the collaboration relationship between actors in implementing women’s protection policies. The results of hypothesis testing show that there is a positive relationship between actor collaboration in policy implementation. The most influential actors are the local government with an influence value of 0.741* and the mass media with an influence value of 0.530*.